Modeling Thermal Behavior of Mass Concrete Structures at Early Age. Issue 6 (June 2022) - Alper Yikici, Tahsin; Sezer, Hayri; (Roger) Chen, Hung-Liang
In this study, a three-dimensional (3D) mathematical model based on conduction heat transfer in a solid is developed to predict the temperature profile of large concrete elements during the hydration process at early ages. Four different concrete mix designs are tested in the laboratory and on site. Heat of hydration and activation energy of each concrete mix is determined in the laboratory and temperature dependent thermo-physical parameters are considered in the simulations. The transient 3D conduction heat transfer equation with a heat generation source term is discretized by using finite volume method. The mathematical model is validated with temperature-time histories measured from four 1.8 m cube concrete blocks that are cast on site. Results obtained from the 3D model show that variable thermal properties are considered to accurately predict the temperature gradients. According to the analysis, the numerical model demonstrates that it can produce accurate predictions for temperature analysis within the 1.8 m large concrete elements.